Kakucs-Turján: a multi-layered settlement in Central Hungary - Jaeger, Mateusz; Staniuk, Robert; Filatova, Sofia; Kulcsár, Gabriella (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
Investigations of the settlement of Kakucs-Turján have applied a multi-disciplinary approach to recognize the everyday reality of communities living in Early and Middle Bronze Age Hungary. Field prospection and preliminary excavations allowed characterization of the overall site parameters, while the subsequent excavation seasons provided evidence of a complex settlement history wherein a major transition from behaviors producing a flat to a multilayered site was identified as a major turning point. Analyses of material culture and botanical remains point to stable lifestyles and subsistence practices across generations of inhabitation of the settlement within which differential access to exotic resources and non-local objects was part of the way of life. This paper provides a state-of-the-art overview summarizing the main findings of the focal points of research at Kakucs-Turján.
Keywords: Hungarian Bronze Age; Tell Settlement; Vatya Culture